(untitled) (Studia theodisca, 2012)
The journalist and popular travel writer, Egon Erwin Kisch, and the well-known novelist and short story writer Anna Seghers were among the many left wing and communist intellectuals for whom Mexico was a haven during the Hitler years. Kisch traveled extensively in Mexico, immersed himself in its history and culture and interpreted Mexico for the other German exiles. On her return from exile Seghers became an important mediator in the GDR of Mexican and South American culture and a strong voice for crosscultural understanding